2011
DOI: 10.1007/s10157-011-0529-7
|View full text |Cite
|
Sign up to set email alerts
|

A case of perforative peritonitis caused by a piece of bamboo in a patient on peritoneal dialysis

Abstract: We report a case of peritonitis resulting from colon perforation caused by ingestion of a rare foreign body in a patient on peritoneal dialysis (PD). A 72-year-old woman on PD was hospitalized with abdominal pain and cloudy PD fluid (PDF). Although conventional antibiotic therapy was started because of a diagnosis of infectious peritonitis, low-grade fever, abdominal pain and a high number of white blood cells in PDF persisted. On day 3, anaerobic bacteria were recognized on bacterial culture of PDF, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In the ISPD guidelines, anaerobic growth is frequently linked to intra-abdominal events requiring surgical attention [11,12] because delayed intervention could be detrimental [17,18]. However, in our case series, only 2 episodes had GI lesions identified.…”
Section: Discussionmentioning
confidence: 66%
“…In the ISPD guidelines, anaerobic growth is frequently linked to intra-abdominal events requiring surgical attention [11,12] because delayed intervention could be detrimental [17,18]. However, in our case series, only 2 episodes had GI lesions identified.…”
Section: Discussionmentioning
confidence: 66%
“…Chang et al [ 4 ] reported surgical intervention due to unrelieved abdominal symptoms and a great amount of turbid ascites after PD catheter removal in 2 cases of Pseudomonas -related peritonitis, and both patients survived. Suzuki et al [ 5 ] presented a rare case of peritonitis secondary to colon perforation caused by ingestion of a piece of bamboo in a PD patient; the PD catheter was removed, followed by peritoneal lavage and continuous abdominal drainage, and the patient finally recovered.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, if an episode of peritonitis is secondary to acute abdomen such as gastric or intestinal perforation, appropriate procedures should follow surgical principles, and the aim should be effective source control, which refers to drainage of infected foci, controlling ongoing peritoneal contamination and restoration of anatomic and physiological function [ 6 ]. The PD catheter needs to be removed concomitantly, as in the case shown by Suzuki et al [ 5 ]. While an episode of refractory PD-related peritonitis is a primary one, the situation can be more complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Touch contamination during PD fluid exchange is the most common cause of PD-related peritonitis [2]. Additionally, while uncommon, intestinal perforation is a critical complication that is difficult to diagnose in PD patients [3]. It has been reported that the mortality rate of perforative peritonitis is quite high [4].…”
Section: Introductionmentioning
confidence: 99%